Quality Analysis of Outpatient Care at Kepulauan Seribu General Hospital based on Malcolm Baldrige Criteria - Ghamal Ahmad Pramana; Dumilah Ayuningtyas (Asian Journal of Social and Humanities, 2023)
The outpatient unit is a part of the hospital. The outpatient unit has an important role because it is the first door or medium for contact and interaction with service users or patients. Outpatient care is also an entry point for other inpatient services. Seribu Islands Regional General Hospital as the only hospital in the Thousand Islands region has not yet reached the required minimum outpatient service standard. This study aims to analyze the quality of outpatient care at Seribu Islands Hospital with the criteria of Malcolm Baldrige. The criteria for evaluating organizations are based on seven criteria, namely leadership, strategic planning, customer focus, measurement, analysis, and knowledge management, staff focus, process management, and performance results. This study uses a descriptive analytic research design with quantitative and qualitative approaches. The data collected was obtained through questionnaires, in-depth interviews, and document review. The results of the study using the Malcolm Baldrige Criteria showed that Seribu Islands Hospital won a score of 379.83 out of a maximum of 1000. This means that for hospital performance assessment based on MBNQA, Kepulauan Seribu Hospital won the average title and was included in the Early Improvement category (point scale 376-475 ). Early improvement means that Seribu Islands Hospital is in a position of early stage improvement in the health service sector. For this reason, it is recommended that Thousand Islands Hospital develop strong leadership and good teamwork in order to determine the right strategic plan.